Multiscale connectivity characterization of marine shales in southern China by fluid intrusion, small-angle neutron scattering (SANS), and FIB-SEM. (February 2020) - Sun, Mengdi; Zhang, Linhao; Hu, Qinhong; Pan, Zhejun; Yu, Bingsong; Sun, Liangwei; Bai, Liangfei; Fu, Haijiao; Zhang, Yifan; Zhang, Cong; Cheng, Gang
Abstract: An evaluation of shale pore connectivity is essential for predicting the production behavior and optimizing the development plan of shale gas. To systematically investigate the multiscale connectivity characteristics and controlling factors, complementary tests were conducted on four overmature marine shale samples from southern China (one each from Longmaxi Formation and Wufeng Formation, and two from Niutitang Formation) with different maturity and composition. The methods included mercury intrusion capillary pressure (MICP), spontaneous imbibition with deionized water and n-decane, saturated diffusion distribution with seven nano-sized tracers, N2 physisorption, small-angle neutron scattering (SANS), and focused ion beam-scanning electron microscopy (FIB-SEM) tomography. Moreover, a novel repeated MICP measurement technique was developed and used to evaluate the pore connectivity from the distribution behavior of residual mercury. Results indicate that the connectivity loss of hydrophilic pore networks owing to an increased maturity and the compaction causes pore shrinkage and bond breakage between pore networks. According to the three-dimensional reconstruction and pore network extraction of FIB-SEM images, pores in organic matter (OM) have a good pore connectivity, but the minerals surrounding the OM reduce the overall pore connectivity of the shale matrix. By evaluating the pore connectivity using different methods, the hydrocarbon migration pattern in overmature marine shales was established. Our results imply that in addition to creating induced fracture networks, effectively connecting induced fractures with preexisting microcracks or joint sets between OM pore networks and transport pores can also be used to enhance overall pore connectivity. Microwave heating in shale reservoirs may be an effective way of further improving the production and recovery of hydrocarbons. Highlights: Pore connectivity for shale samples from marine formations was studied with complementary methods at multiple scales. A novel repeated MICP measurement was developed to evaluate the pore connectivity. Shale pore connectivity was indicated from diffusion distribution of seven nanotracers. Controlling factors of pore connectivity were discussed by visual and quantitative techniques. Hydrocarbon migration pattern was established based on pore connectivity of shale.